(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Varroa destructor mite causes mortality of Apis mellifera bees throughout the world. Its greatest damage to these colonies has been reported in European countries and North America. The impact of the mite is related to the climate and the bee race on each region in which the plague has been established. Varroa causes little damage to the colonies of africanized honeybees in Brazil and the levels of infestation are relatively small and stable. The reproductive ability of Varroa females was evaluated in pupae of workers of 17-18 days of age, obtained from eight beehives of africanized bees for twelve months. The average number of offspring (deutonymphs, protonymphs and eggs) each Varroa produced was 3.18 ± 0.19. The average total number of deutonymph and protonymph was, respectively, 1.57 ± 0.15 and 1.61 ± 0.14. The levels of infestation demonstrated that the plague continue reaching low levels, the average was 4.11 ± 3.42.